KEPUASAN HIDUP GURU HONORER DI MI SINDON 2 NGEMPLAK BOYOLALI - Novita Sari, Eka; Riskiana Putri, Dhian; Purnomosidi, Faqih (Universitas Sahid Surakarta, 2023)
This study aims to explain the life satisfaction of honorary teachers at MI Sindon 2 Ngemplak Boyolali. Teachers have a significant role in teaching science, guiding, and training students. Even teachers are also referred to as unsung heroes. Teachers are divided into permanent teachers (civil servants) and honorary teachers (wiyata bakti). This study used a qualitative approach with observation and interview methods based on aspects of live satisfaction according to Hurlock and Diener-Bieswas. The subjects were six honorary teachers as the primary informants and two school principals and administrative staff as supporting informants.The results indicate that life satisfaction for honorary teachers at MI Sindon 2 Ngemplak Boyolali is good. The way to deal with these problems is to be grateful and willing to do a job.